(untitled) (Bangladesh Journal of Zoology, 2020)
Four species of damselfish viz., Pomacentrus proteus Allen, 1991; Pomacentrus similis Allen, 1991; Stegastes obreptus (Whitley, 1948) and Pomacentrus adelus Allen, 1991 have been recorded for the first time from the marine water of Bangladesh in the Saint Martin’s Island. The species were observed and captured photographs during monthly underwater survey from January to March 2018 on coral associated fishes in the Saint Martin’s Island located at the northern Bay of Bengal, Bangladesh. Bangladesh J. Zool. 48(1): 57-66, 2020